2020
DOI: 10.3390/v12090962
|View full text |Cite
|
Sign up to set email alerts
|

Human Papillomavirus (HPV) DNA Detection Using Self-Sampling Devices in Women Undergoing Long Term Immunosuppressive Therapy

Abstract: Immunosuppression is a risk factor of persistent human papillomavirus (HPV) infections, which might lead to development of (pre)malignant lesions of the cervix and lower anogenital tract. Results of HPV DNA testing using cervicovaginal self-samples are comparable to those that are clinician-obtained and therefore might be used in cervical screening. The aim of this study was to assess the prevalence of high-risk HPV (hrHPV) infections, their risk factors and the genotypes distribution among women undergoing im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…The hrHPV prevalence in RTRs varies in different areas. Although some studies reported no difference in hrHPV infection rates between kidney transplant recipients and their matched controls ( 11 13 ), most studies confirmed a significantly higher prevalence of cervical hrHPV among RTRs ( 14 17 ). The 2019 American Society of Colposcopy and Cervical Pathology (ASCCP) consensus guidelines emphasized the importance of regular cervical cancer screening for patients with immunosuppression ( 18 ).…”
Section: Introductionmentioning
confidence: 94%
“…The hrHPV prevalence in RTRs varies in different areas. Although some studies reported no difference in hrHPV infection rates between kidney transplant recipients and their matched controls ( 11 13 ), most studies confirmed a significantly higher prevalence of cervical hrHPV among RTRs ( 14 17 ). The 2019 American Society of Colposcopy and Cervical Pathology (ASCCP) consensus guidelines emphasized the importance of regular cervical cancer screening for patients with immunosuppression ( 18 ).…”
Section: Introductionmentioning
confidence: 94%
“…HPV 45 was the most common genotype (3.3%) and only one patient tested positive for HPV 16 (1.7%) [20]. Nevertheless, in other European studies, including renal-transplant women and patients undergoing immunosuppressive therapies for at least 3 months, HPV 16 was dominant [19,23].…”
Section: Discussionmentioning
confidence: 89%
“…The exclusion criteria constituted of menstruation on the day of a possible enrollment or a history of cervical cancer. The patients invited to participate in the study were chosen randomly based on their presence in the Institute of Transplantology or the outpatient clinics during the enrollment period as there is no nationwide registry of immunocompromised patients in Poland [ 19 ].…”
Section: Methodsmentioning
confidence: 99%